2017
DOI: 10.1002/chem.201701392
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Medicinal Potential of Two Ruthenium(II) Polypyridine Complexes as One‐ and Two‐Photon Photodynamic Therapy Photosensitizers

Abstract: Two [Ru(phen) dppz] derivatives (phen=1,10-phenantroline, dppz=dipyrido[3,2-a:2',3'-c]phenazine) with different functional groups on the dppz ligand [dppz-7,8-(OMe) (1), dppz-7,8-(OH) (2)] have been synthesized, characterized and investigated as photosensitizers (PSs) for photodynamic therapy (PDT) against cancer. Both complexes showed intense red phosphorescence and promising singlet oxygen ( O ) quantum yields of 75 % (1) and 54 % (2) in acetonitrile. Complex 1 (logP =-0.52, 2.4 nmol Ru per mg protein) was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 98 publications
5
75
0
2
Order By: Relevance
“…However, multiphoton PDT also has limitations, posing new challenges for its clinical application. Unlike one photon PDT that can be easily carried out with low power lasers and LEDs, two photon PDT requires higher power lasers for successful photosensitization . Although the area irradiated with 2‐photon light can be highly specific, the volume of irradiated tissue is very small (≈1 μm 3 ), which will necessiate new rastering techniques if wide areas are to be treated.…”
Section: Challenges For Clinical Translation Of Photochemotherapeuticmentioning
confidence: 99%
“…However, multiphoton PDT also has limitations, posing new challenges for its clinical application. Unlike one photon PDT that can be easily carried out with low power lasers and LEDs, two photon PDT requires higher power lasers for successful photosensitization . Although the area irradiated with 2‐photon light can be highly specific, the volume of irradiated tissue is very small (≈1 μm 3 ), which will necessiate new rastering techniques if wide areas are to be treated.…”
Section: Challenges For Clinical Translation Of Photochemotherapeuticmentioning
confidence: 99%
“…PDT relies on the use of a photosensitizer agent (PS), that can be triggered by irradiation with low‐energy light to generate cytotoxic species, such as reactive oxygen species (ROS), thus providing a complete spatial and temporal control over the generation of the toxic molecule . Generally, light‐activated PSs can react with the molecular oxygen leading to the formation of ROS through two distinct pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Although [Ru(bpy) 2 (dppz)] 2+ and [Ru(phen) 2 (dppz)] 2+ bind DNA strongly, they have generally exhibited low cytotoxicity against eukaryotic cells, with a number of studies indicating that the low cytotoxicity was due to their poor cellular uptake . Puckett and Barton demonstrated that these complexes enter eukaryotic cells by passive diffusion, and that the uptake can be enhanced by increasing the lipophilicity of the complex, for example, by substituting the bpy or phen ligands with 4,7‐diphenyl‐1,10‐phenanthroline (DIP) .…”
Section: Introductionmentioning
confidence: 99%
“…To increase the antimicrobial activity of [Ru(2,9‐Me 2 phen) 2 (dppz)] 2+ , the 2,9‐Me 2 phen ligands could be replaced with a more lipophilic ligand such as DIP. However, this would also significantly increase the toxicity of the ruthenium complex to eukaryotic systems . In addition, a number of studies have also demonstrated that the cellular localisation of polypyridylruthenium(II) complexes in eukaryotic cells is significantly modulated by the lipophilicity .…”
Section: Introductionmentioning
confidence: 99%